PENGARUH KEPEMIMPINAN PARTISIPATIF DAN BUDAYA ORGANISASI TERHADAP EFEKTIVITAS ORGANISASI PADA SEKOLAH MENENGAH ATAS (SMA) DAN SEKOLAH MENENGAH KEJURUAN (SMK) PASUNDAN - Eden Komarudin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pasundan Bandung, 2018)
The problem in this study, the low effectiveness of the organization due to the ineffectiveness of participative leadership and organizational culture is not optimal in High School (SMA) and Vocational School (SMK) Pasundan. The method used in this research is descriptive and explanatory survey method, namely with the aim to provide an overview to better understand, produce certain symptoms or problems, so this study is not only to test the results of the study but produce a deeper understanding of the phenomenon under study on the Analysis Effect of Participatory Leadership and Organizational Culture on Organizational Effectiveness High School (SMA) and Vocational School (SMK) Pasundan based theories and concepts proposed. The research proves that the influence of participative leadership variables (X1) on the effectiveness of organizations by 0.334 while organizational culture variables (X2) influence of 0.285 or 28.5%, bringing the total major influence on the effectiveness of the organization both variables is equal to 0619 or 61.9% while the error for this model of 0381, or 38.1% due to the variable outside of research, with much the relationship between the two variables participative leadership and organizational culture for 0656, or 65.6%. If leadership partisifatip increases one unit will increase the effectiveness of organizations by 0578 satuan.Dan, if the culture of the organization increases the unit will improve organizational effectiveness by 0534 units. So that the total effect of the variable of organizational culture on organizational effectiveness is equal to 0454. Participatory leadership and significant positive effect on organizational effectiveness School (SMA) and Vocational School (SMK) Pasundan. The dimensions of participatory leadership that gives the most impact is the dimension develop expertise, followed by small dimensions which influence the dimensions of the team developing the organization, the dimensions of building trust and responsibility and creative vision. Partially Organizational Culture has a positive and significant influence on the effectiveness of the organization High School (SMA) and Vocational School (SMK) Pasundan. The characteristics of organizational culture that gives the most impact is characteristic of a meeting or meetings on time. Followed by minor characteristics that influence the characteristics of a sense of security with pekerjaa, characteristic pride and appreciated, characteristic attention to costs, friendly characteristics, the characteristics of organizing the work itself, the characteristics devote all abilities.